LOW PLATELETCRIT IS ASSOCIATED WITH REDUCED PROGRESSION – FREE AND OVERALL SURVIVAL IN CHRONIC LYMPHOCYTIC LEUKEMIA: Plateletcrit and Chronic Lymphocytic Leukemia - Ozbalci, Demircan; Alanoglu, Emine Guchan; Findos, Eda; Eroglu, Hande Nur (Journal of Medical Biochemistry, 2022)
BACKGROUD Alterations of plateletcrit and mean platelet volume (MPV) and pathogenesis of chronic lymphocytic leukemia (CLL) have been linked to various inflammatory disorders. The prognostic impact of plateletcrit and MPV were evaluated. METHODS MPV and plateletcrit levels of both CLL and control group were compared and then in CLL patients, additional diseases, leukocyte count, platelet count, lactate dehydrogenase, Rai stage, progression-free and overall survival, mutations, if any, and chemotherapy, if any, were recorded. Then, the relationship between MPV and plateletcrit values and these parameters were evaluated in CLL patients. RESULTS Platelet and plateletcrit values ​​were found to be significantly lower in CLL patients than the control group (p<0.001) for both. Plateletcrit and MPV values of patients who did not receive chemotherapy were higher than those who received chemotherapy (p=0.03, p=0.02, respectively). Being over 75 years old, plateletcrit value less than 0.1565 %, platelet level below 175x 109/L, and leukocyte count greater than 53.5 x 109/L was found to significantly reduce overall survival. Male gender, each stage increase, plateletcrit less than 0.1565 % and leukocyte count greater than 53.5 x 109/L was related to reduced treatment-free survival in CLL patients. CONCLUSION Plateletcrit is a viable prognostic marker for defining both treatment free and overall survival.